2017
DOI: 10.18203/2320-1770.ijrcog20175865
|View full text |Cite
|
Sign up to set email alerts
|

Gynecological disorders in geriatric women regarding their frequency, diagnosis and management in the state of Himachal Pradesh, India

Abstract: INTRODUCTIONThe word Geriatrics was coined by Dr. Ignatz Natcher an Austrian physician in 1909. However, it was in 1935 that a British doctor Marjory Warren, working in USA first developed the practical concept of geriatric rehabilitation. With her initiation the elderly patients were gradually taken over by teaching hospitals. 1Many studies from developed countries defined older persons as those aged more than 65 years, whereas some use the cut off of 60 yrs. Life expectancy of India is 61 years as compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(19 reference statements)
0
0
0
Order By: Relevance
“…We found that common disorders were pelvic organ prolapse in 50, Ca ovary in 4, Ca cervix in 6, endometrial hyperplasia in 12, cervical polyp in 8, Ca vulva in 7, proliferative endometrium in 13, vulval papilloma in 6 and genital malignancies in 14. Sood et al [11] assessed gynaecological disorders in geriatric women regarding their frequency, diagnosis and management. 224 patients aged 60 years and above were admitted over a period of one year.…”
Section: Discussionmentioning
confidence: 99%
“…We found that common disorders were pelvic organ prolapse in 50, Ca ovary in 4, Ca cervix in 6, endometrial hyperplasia in 12, cervical polyp in 8, Ca vulva in 7, proliferative endometrium in 13, vulval papilloma in 6 and genital malignancies in 14. Sood et al [11] assessed gynaecological disorders in geriatric women regarding their frequency, diagnosis and management. 224 patients aged 60 years and above were admitted over a period of one year.…”
Section: Discussionmentioning
confidence: 99%